PENERAPAN MEKANISME MEDIASI DALAM PROSES PENYELESAIAN SENGKETA KEWENANGAN BADAN PERMUSYARAWATAN DESA DAN KEPALA DESA BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (STUDI KASUS DI DESA JENGGALA, KECAMATAN TANJUNG KABUPATEN LOMBOK UTARA) - ASMAYANDI, ASMAYANDI; SYAIFULLAH, SYAIFULLAH; APRIANI, TITIN (Universitas Mahasaraswati K. Mataram, 2023)
That the potential for overlap in the authority of the BPD and the Head as a form of normative application of Law Number 6 of 2014 is very large, especially if we look at aspects of implementing the functions of the BPD Institution which will coincide with the function of the village head as executor of government in the village. The formulation of the problem in this research is first, How is the Mediation Mechanism Implemented in the Dispute Resolution Process over the Authority of the Village Consultative Body and the Village Head Based on Law Number 6 of 2014 on Village Neighborhoods? And secondly, what are the alternative forms of mediation that can be implemented in the Dispute Resolution Process over the Authority of the Village Consultative Body and the Village Head Based on Law Number 6 of 2014 on Village Neighbors (Case Study in Jenggala Village, Tanjung District, North Lombok Regency) The results of the research conducted by the author show that firstly, the application of a mediation mechanism in resolving authority disputes between the BPD and the Village Head can be carried out on a normative basis contained in the provisions of Article 112 in Article 115 of Law Number 6 of 2014 concerning Villages. Second, alternative forms of mediation in resolving disputes between the Village Head and BPD in Jenggala Village can be implemented in 2 (two) forms, namely, formal mediation and informal mediation. Formal mediation is mediation carried out by the KLU DP2KBPMD Service who acts as the mediator. Meanwhile, informal mediation can be carried out through, firstly, the Village Inter-Institutional Communication Forum (FKAKD), the formation of which was initiated by the BPD based on the provisions of Article 62 of North Lombok Regency Regional Regulation Number 3 of 2019 concerning BPD, and secondly through the Village Krama Council based on North Lombok Regent Regulation Number 20 2017 concerning MKD Guidelines.